The Leap of Faith: The Fiscal Foundations of Successful Government in Europe and America - Sven Steinmo (Oxford University Press, 2018)
This is the first book to compare the history of tax compliance in several countries (Sweden, Britain, Italy, Romania, and the United States) The book clearly elaborates the policy lessons from the five cases explored for countries who are currently trying to build successful and effective tax policies Makes the direct connection between historical cases and current policy issues in developed and developing countries Why are citizens in some countries more willing to pay taxes than in other countries? This book examines the history of the relationship between citizens and their states in five countries, (Sweden, Britain, Italy, Romania, and the United States), and demonstrates how and why people in in some countries have come to trust the government with their money while in other countries they do not. The book explores the evolution of this relationship in detail, in each case showing how some governments developed the fiscal and technical capacity to tax their citizens fairly and deliver public services efficiently. In short, how and why some countries became more trustworthy than others. The volume concludes by examining the implications of these five cases for developing countries today and the lessons that can be learned.
Keywords: 330; history of tax; Sweden; Britain; Italy; Romania; United States; tax policies; developed countries; developing countries